1998
DOI: 10.1002/(sici)1099-1212(199805/06)8:3<180::aid-oa421>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The utility of hand and foot bones for the determination of sex and the estimation of stature in a prehistoric population from west-central Illinois

Abstract: This study focuses on hands and feet as indicators of sex and stature for Native Americans, hitherto relatively neglected in this regard. The study was performed on a large, well‐preserved prehistoric skeletal sample from west‐central Illinois. Discriminant functions are presented which determine sex with accuracies exceeding 87%. Those functions are then tested on three other Native American samples and found to have similar high degrees of accuracy. The utility of hand and foot bones for estimation of femur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 18 publications
4
46
0
4
Order By: Relevance
“…Anthropometry as adopted by medical scientistis is described as a technique of expressing the form of human body quantitatively as it is the systematic collection and correlation of measurement of the humanbody [1] . It is highly objective and reliable in the hands of trained The human foot, the foundation of bipedal locomotion, is a highly complex multi bone structure with 26 bones and numerous articulation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometry as adopted by medical scientistis is described as a technique of expressing the form of human body quantitatively as it is the systematic collection and correlation of measurement of the humanbody [1] . It is highly objective and reliable in the hands of trained The human foot, the foundation of bipedal locomotion, is a highly complex multi bone structure with 26 bones and numerous articulation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when the pelvic region or cranium, which are the most accurate indicators of sex [1], are missing or fragmentary, it is useful to have appropriate tools for sex assignment based on other features. Furthermore, it has been established by other researchers that population-specific methods are necessary due to variation in sexual dimorphism and activity related morphology between populations [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The population specificity of the discriminant function method has been noted by many authors. [10][11][12][13] Descriptive statistics showed that the size of the calcaneus in is dimorphic between the sexes. Besides the merits of the calcaneus in excavations, several statistical studies of the calcaneus suggest that a discriminant function equation using this bone's metric data is able to identify sex with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Authors Total Original Accuracy (%) Black and White Americans Steele [5] 79 White South Africans Bidmos and Asala [2] 85 Black South Africans Bidmos and Asala [16] 83.5 Northern Italians Gualdi-Russo [15] 90.7 Central Europeans Riepert et al [15] 80 Native Americans Wilbur [18] 84.5 Han population of Sichuan Province Zhang et al [25] 83 North Indians Present Study 100(Right and Left Stepwise)…”
Section: Populationsmentioning
confidence: 99%